A Case Report of COVID-19 in a Living Kidney Transplant Recipient: A Challenging Case with Complete Rehabilitation. (17th January 2022) - Poor Zamany Nejat Kermaney, Mahtab; Hamidi Madani, Mohammad; Bonakdar Hashemi, Milad; Zadmehr, Alireza; Dadpour, Mehdi; Roodneshin, Fatemeh
Abstract : Adjustment of immunosuppressive and COVID-19 treatment in terms of drug interactions is still challenging. Herein, we report a 45-year-old woman with end-stage renal disease due to autosomal dominant polycystic diseases (ADPKD) with COVID-19 and pulmonary involvement following kidney transplantation. The patient was properly treated by discontinuation of immunosuppressive drugs, bronchoscopy, and high volume of blood transfusions. The fact that we quickly used early intubation and a new treatment regimen that suppressed immune systems may help physicians develop optimal treatment strategies for similar severe cases. However, this treatment method requires more detailed evaluations due to the contradictory results in reviewing other studies.